Bispecific antibodies combined with chemotherapy in solid tumor treatment, the path forward? - Yan, Yici; Yuan, Jing; Peng, Yanyang; Zhou, Chenxi; Liu, Xinbo; Sun, Leitao; Song, Qiaoling (Frontiers in Immunology, 2025)
BackgroundBispecific antibodies (bsAbs) introduced a novel strategy in anticancer therapy when chemotherapy alone could not meet life expectancy. Nonetheless, the efficacy of monotherapy was limited, and the safety profile of bsAbs combined with chemotherapy remained uncertain.MethodsLiterature retrieval was carried out through PubMed, Embase, and Cochrane from inception to January, 2025. Progression-free survival (PFS), overall survival (OS), and overall response rate (ORR), along with adverse effects (AEs), were utilized to assess the efficacy and safety. Publication bias was calculated using Funnel plots and Egger’s test. Heterogeneity was examined through subgroup and sensitivity analyses. The protocol was preregistered in the International Prospective Register of Systematic Reviews (CRD42025633628).ResultsA total of 8 eligible clinical studies with 2,495 patients were included. Compared with chemotherapy alone, bsAb+chemotherapy exhibited positive outcomes in PFS (hazard ratio (HR): 0.52; 95% confidence interval (CI): 0.44-0.60; p<0.01), OS (HR: 0.67, 95% CI: 0.57-0.77; p<0.01), and ORR (HR: 0.31, 95% CI: 0.16-0.47; p<0.01). Subgroup analysis revealed that female patients, Asian patients, those under 65 years of age, and patients treated with IgG-like bsAb were more likely to benefit from the survival advantages of bsAb+chemotherapy. Despite the occurrence of leukopenia, metabolism-related, and skin-related AEs, RR of AEs in other systems showed no statistical significance.ConclusionBsAb+chemotherapy was superior to chemotherapy alone, especially in female patients, Asian patients, those under 65 years of age, and patients receiving IgG-like bsAb. Additionally, while the AEs associated with bsAb+chemotherapy are generally manageable, there is still room for improvement.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025633628.